COMPARISON STUDY OF COMPRESSIVE STRENGTH OF REDBRICKS AND LIGHT BRICKS - Mohammad Djaelani; Didit Darmawan; Ella Anastasya Sinambela; Rahayu Mardikaningsih (Universitas Mahendradatta, 2022)
The progress of development in Indonesia is very rapid, building materials are demanded tohave very good quality. The purpose of this study is to determine the comparison of the compressivestrength of red brick and lightweight brick as it should be in the field of development that affects economicdevelopment, in this study it is very useful for the community when buying materials. This type ofresearch is qualitative. The data was obtained by conducting research on data analysis techniques.used is to use a formula to determine the value of compressive strength. The results showed that redbricks and light bricks had different compressive strength values. Lightweight bricks which are heatedin the sun for 7 days have a compressive strength value of 58.916 kg/cm², while those that are soakedin water for 4 days have a compressive strength value of 36.256 kg/cm² and those which are blown inthe wind for 28 days have a compressive strength value of 45.32 kg/cm². cm². for red bricks that aredried for 5 days and then burned for 1 day. after the red bricks are ripe and then heated in the sun for 7days has a compressive strength value of 33,709 kg/cm² while those that are soaked for 4 days have acompressive strength value of 29,495 kg/cm² a